REKOMENDASI PENGADAAN BARANG PADA MEBEL MITRA AGUNG MENGGUNAKAN METODE MARKET BASKET ANALYSIS - Annisa Christi Damayanti; Kurnia Paranita Kartika; Sabitul Kirom (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2022)
Abstract Mitra Agung Furniture is one of the companies engaged in the sale of home furnishing goods in the city of Blitar. There are goods sold in furniture that are self-produced, and there are goods that are entrusted by other people. The number of items in the Mitra Agung furniture warehouse is quite a lot, so that in organizing the items in the warehouse, they will be grouped by type of goods. Therefore, if you want to know the appropriate stock of goods, you must contact the warehouse and ask for the stock of goods needed. This method is unstructured and takes a long time. Then an application for recommendation of goods was made using the market basket analysis method, an application made web-based which uses bootstrap as the interface design and Mysql as the database. So that good results are obtained from the system that is made according to the test results of validators and users and can be a solution to problems in furniture. Keywords: Bootstrap, Mysql, Market Basket Analysis, website